2017
DOI: 10.1111/bcp.13364
|View full text |Cite
|
Sign up to set email alerts
|

Use of antibiotics during pregnancy and the risk of major congenital malformations: a population based cohort study

Abstract: Clindamycin, doxycycline, quinolones, macrolides and phenoxymethylpenicillin in utero exposure were linked to organ-specific malformations. Amoxicillin, cephalosporins and nitrofurantoin were not associated with MCMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
91
4
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 60 publications
9
91
4
5
Order By: Relevance
“…Second, biological plausibility has been reported for each association seen in our study which strengthen our findings .…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Second, biological plausibility has been reported for each association seen in our study which strengthen our findings .…”
supporting
confidence: 90%
“…Finally, no increased risk of major congenital malformations following in utero exposure to fluoroquinolone class has been reported in eight studies as stated in our manuscript . Though, those previous studies, including published meta‐analyses, were limited by several methodological flaws (low power, recall and indication bias) as pointed out in our paper, their findings were overall similar to ours .…”
supporting
confidence: 85%
“…Several animal model studies have shown possible teratogenic effects. [14][15][16] In the present study we wished to further explore this topic by performing an updated literature search and metaanalysis of the human studies, and in this way provide practical guidance about the use of these agents in pregnancy. In 2009, Bar-Oz et al performed a meta-analysis of the available data regarding the effect of fluoroquinolones, taken during the first trimester, on fetal malformations and pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In a 2017 issue of Br J Clin Pharmacol , Muanda et al published an outstanding study titled “Use of antibiotics during pregnancy and the risk of major congenital malformations: a population based cohort study.” The objective of this study was to quantify the association between exposure to gestational antibiotics and the risk of major congenital malformations (MCMs) using the Quebec pregnancy cohort (1998‐2008). They found that “Doxycycline exposure increased the risk of circulatory system malformation, cardiac malformations and ventricular/atrial septal defect (aOR 2.38, 95% CI 1.21‐4.67, 9 exposed cases; aOR 2.46, 95% CI 1.21‐4.99, 8 exposed cases; aOR 3.19, 95% CI 1.57‐6.48, 8 exposed cases, respectively).” The authors concluded that “in utero exposure to clindamycin, doxycycline, macrolide, quinolone and phenoxymethylpenicillin increased the risk of organ‐specific MCMS in infants.”…”
mentioning
confidence: 99%
“…The findings and conclusions, specifically regarding doxycycline, presented in the article by Muanda et al should be interpreted with caution for the following reasons: The start of doxycycline treatment and the event (MCM) onset date are unknown. The authors used “prevalence odds ratios” to quantify the association between ventricular/atrial septal defect and exposure to the doxycycline within the first trimester (12 weeks) of pregnancy.…”
mentioning
confidence: 99%